2020
DOI: 10.1002/2211-5463.12997
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C regulates the cytotoxicity of infection‐induced endothelial‐derived β‐amyloid

Abstract: Infection of pulmonary endothelial cells by Pseudomonas aeruginosa induces the production and release of cytotoxic oligomeric tau and Aβ from the endothelial cells. Cystatin C, which is also secreted by the endothelial cells, can suppress the cytotoxic activity of Aβ. Whether cystatin C directly impacts oligomeric tau remains to be determined. Image produced with BioRender.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…We have previously shown that Gram-positive and Gram-negative organisms that cause pneumonia trigger the release of cytotoxic tau variants from lung endothelium, as quantified using Western blotting with antibodies selective for various tau species (e.g., TOC1, TauC3, Tau5, and T22) (17,31). In a recent study, we determined the 'bioactivity' of endothelium-derived tau and amyloid species released from lung endothelium after infection with P. aeruginosa strain variants (32).…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that Gram-positive and Gram-negative organisms that cause pneumonia trigger the release of cytotoxic tau variants from lung endothelium, as quantified using Western blotting with antibodies selective for various tau species (e.g., TOC1, TauC3, Tau5, and T22) (17,31). In a recent study, we determined the 'bioactivity' of endothelium-derived tau and amyloid species released from lung endothelium after infection with P. aeruginosa strain variants (32).…”
Section: Resultsmentioning
confidence: 99%
“…Lung endothelium produces Aβ ( 15 , 17 , 23 ). Amyloid concentrations are increased in the bronchoalveolar lavage fluid and plasma of patients with pneumonia ( 18 , 39 ), and here, we observed increased Aβ 42 in the circulation of wild-type rats and increased Aβ 42/40 ratios in both wild-type and GSAP KO rats postinfection.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the increase in circulating amyloids during infection cannot be specifically attributed to their production by lung endothelium. As Aβ 40 and Aβ 42 can be cytotoxic to the host ( 23 ), these infection-elicited amyloids may be an independent cause of injury to the alveolar-capillary barrier. Amyloids can also have antimicrobial properties ( 11 15 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation